Transitions to Sustainability - Mancebo, François; Sachs, Ignacy (Springer Netherlands : Imprint: Springer, 2015)
Based on debates and conclusions of the three most recent Rencontres Internationales de Reims on Sustainability Studies, organized by the International Research Center on Sustainability (IRCS) at Rheims University (www.sustainability-studies.org), this book examines the challenges and the conditions of a sound transition toward sustainability. The editors and contributors begin from the perspective that fostering sustainability requires more than the academic aims of developing the right markets, institutions and metrics, it requires social momentum. This raises many questions in need of clear and complete answers: How can social justice be linked with sustainability policies? What governance tools are needed to do so? What is the linkage between the different decision-making levels? The book is divided into three sections. The first part, Meeting the Challenges of the Anthropocene: Back to planning? identifies new forms of planning; forms which could foster the transition to sustainability. Because the stakes are high - nothing less than the type of society we choose to promote in the long term - planning should be designed as a political process rather than just a technical or economic program. An important question is Can sustainability planning be considered as an emerging norm at the international level? The second section, Towards a New Social Contract, addresses the point that present generations are held accountable by future generations, and discusses strategies for designing and adopting a pathway to sustainability. A chapter entitled Insights for a Better Future in an Unfair World addresses the challenges of combining sustainability policies with social justice. The third section, Some Governance Issues, addresses global energy governance, multi-stakeholder governance for sustainable mobility, and territorial governance.